La recaudación tributaria y su relación con la inversión pública de la región Loreto periodo 2019 – 2022 - Ramos Bardales, William Jimy (2025)
The Loreto region is currently facing a situation of variability in tax collection, which has generated challenges in the budget allocation for public investment. The purpose of this work is to identify the relationship between tax collection and public investment in the Loreto region in the period 2019-2022, with a correlational level, non-experimental design and quantitative approach. In which it is concluded that the analysis carried out on tax collection and public investment in the Loreto region during the period 2019-2022 does not reveal a significant relationship between both variables at a global level. However, a very high and significant correlation was identified between the collection of indirect taxes and public investment, which shows their impact on the financing of public spending. Direct taxes represented, on average, 65.98% of total collection, consolidating themselves as the main source of tax revenue, while public investment grew by 63.1% in the same period, reflecting a sustained increase in the allocation of resources. However, other taxes did not show a statistically significant relationship with public investment, suggesting the need to review their structure and contribution to total revenue.